Current state of ichthyofauna and use of aquatic bioresources in the Khrystoforivske Reservoir (Bokovenka River, Dnipro basin) - D. Kobyakov; О. Khristov; R. Novitskyi; O. Bozhko (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To investigate the current state of the ichthyofauna in the Khrystoforivske Reservoir (nearshore and pelagic fish communities), the peculiarities of the distribution of fish communities, their abundance, as well as bioproduction capabilities, the prospects for further fisheries use of the reservoir, considering the ecologically balanced load on the aquatic ecosystem.